(untitled) (Al-Qamar, 2025)
The global climate crisis has become one of the defining concerns of the modern age, affecting ecosystems, agriculture, health, and the stability of societies. Pakistan, frequently listed among the most climate-vulnerable nations, faces acute risks that cannot be addressed solely through scientific innovation or administrative reforms. A durable response requires drawing upon ethical and cultural traditions that can inspire collective responsibility. Islamic sources, particularly the Qur’ān and the Prophetic Sunnah, present a coherent vision of ecological care, emphasizing mīzān (equilibrium), iḥsān (moral excellence), and the rejection of fasād (corruption and harm). Using a historical-analytical method, this study explores environmental practices exemplified in the Prophetic era, including water management, afforestation, regulated grazing, and communal stewardship. It further examines how these principles were institutionalized during the governance of the Rightly Guided Caliphs, and later expanded under Abbasid and Ottoman rule. The analysis highlights their relevance for contemporary Pakistan, particularly in designing sustainable policies and fostering social awareness. The paper ultimately argues for an integrated framework in which Islamic ethical teachings complement modern environmental science, providing a holistic pathway toward resilience in the face of escalating climate threats.